DC characteristics of ALD-grown Al2O3/AlGaN/GaN MIS-HEMTs and HEMTs at 600 °C in air. (13th October 2016) - Suria, Ateeq J; Yalamarthy, Ananth Saran; So, Hongyun; Senesky, Debbie G
Abstract: To the best of our knowledge, the 600 °C device characteristics detailed here reflect the highest operation temperature reported for AlGaN/GaN metal-insulator-semiconductor high electron mobility transistors (MIS-HEMTs) in air which supports the realization of electronics for high-temperature applications (e.g., space exploration, combustion and downhole). The high-temperature response of Al2 O3 /AlGaN/GaN MIS-HEMTs with Al2 O3 deposited by plasma-enhanced atomic layer deposition (ALD) as the gate dielectric and passivation layers was examined here. More specifically, the DC current–voltage response and the threshold voltage characteristics of the MIS-HEMTs were evaluated to temperatures up to 600 °C in air. For comparison, the response of AlGaN/GaN HEMTs without the ALD Al2 O3 layer was also measured. It was observed that the HEMTs failed above 300 °C accompanied by a ∼500 times increase in leakage current and observation of bubbles formed in active region of gate. On the contrary, the MIS-HEMTs continued to operate normally up to 600 °C. However, within the 30 min period exposed to 600 °C the MIS-HEMT degraded permanently. This was observed at 20 °C after return from operation at 600 °C as a change in threshold voltage and saturation drain current. The failure of the HEMTs is suggested to be due to the diffusion of gate metals (Ni and Au) into the active regions of the AlGaN/GaN heterostructure, which creates additional leakage current pathways. The impact of strain relaxation and interfacial trapped charges on threshold voltage as a function of temperature was studied using an energy band-gap model. The ALD Al2 O3 gate dielectric layer acts as a diffusion barrier to the Ni and Au gate metals, thus enabling short-term operation of MIS-HEMTs to 600 °C, the highest operation temperature reported for this device architecture to date.